1994
DOI: 10.1073/pnas.91.23.10903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ech-42, a Trichoderma harzianum endochitinase gene expressed during mycoparasitism.

Abstract: The soil fungus Trichoderma harzianum has been shown to act as a mycoparasite against a range of economically important aerial and soil-borne plant pathogens, being successfully used in the field and greenhouse (1-3). Different factors involved in the antagonistic properties of Trichoderma have been identified, including antibiotics (4-8) and hydrolytic enzymes such as 1,3-3-glucanases, proteases, and chitinases (9).The interaction between Trichoderma and its host is first detectable as chemotropic growth of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(172 citation statements)
references
References 33 publications
10
161
0
1
Order By: Relevance
“…Introduction of multiple copies of the endochitinase chit33 in T. harzianum also resulted in increased biocontrol ability (Dana et al 2001). In contrast, no difference was observed between T. atroviride ech42 overexpression mutants, deletion mutants and wild type (Carsolio et al 1999). Although expression of ech42 and secretion of ECH42 protein during in vitro confrontation with a host pathogen implicated a role for this gene in biocontrol (Carsolio et al 1994), recent diffusion studies have shown ech42 to be involved in pathogen signalling , suggesting a more regulatory role for this enzyme.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Introduction of multiple copies of the endochitinase chit33 in T. harzianum also resulted in increased biocontrol ability (Dana et al 2001). In contrast, no difference was observed between T. atroviride ech42 overexpression mutants, deletion mutants and wild type (Carsolio et al 1999). Although expression of ech42 and secretion of ECH42 protein during in vitro confrontation with a host pathogen implicated a role for this gene in biocontrol (Carsolio et al 1994), recent diffusion studies have shown ech42 to be involved in pathogen signalling , suggesting a more regulatory role for this enzyme.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, no difference was observed between T. atroviride ech42 overexpression mutants, deletion mutants and wild type (Carsolio et al 1999). Although expression of ech42 and secretion of ECH42 protein during in vitro confrontation with a host pathogen implicated a role for this gene in biocontrol (Carsolio et al 1994), recent diffusion studies have shown ech42 to be involved in pathogen signalling , suggesting a more regulatory role for this enzyme. Considerable attention also has focused on the ␤-glucanase genes because a large component of the fungal cell wall is composed of ␤-glucans and, therefore, it is likely that ␤-glucanases play a role in cell-wall degradation during mycoparasitism.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ail but one transformant expressed higher levels of chitinase activity in comparison to the wild type récipient strain; the maximum level of increase rose 5-fold. Duplicating the copy number of the entire endochitinase gène under its own regulatory séquences is especially suitable for improving the biocontrol capability of Trichoderma as the highly conserved 42-kDa endochitinase-encoding gène, présent in ail mycophagous species of Trichoderma (Fekete et ai, 1996) has been shown to be specifically triggered in mycoparasitic interactions (Carsolio et al, 1994). Triggering occurs when a spécifie "mycoparasitic" protein complex binds to the promoter séquences of the gène and displaces the binding of a catabolite repressor protein (Lorito et al, 1996).…”
Section: Aims and Methods Of Strain Improvementmentioning
confidence: 99%
“…The fungal cell wall has a cross-linked complex structure composed of chitin, glucans, and other polymers (AGRIOS, 2005). Enzymes that hydrolyze these components play a significant role in cell wall lysis of the pathogens (ADAMS, 2005;CARSOLIO et al, 1994). The antifungal activity and highly biocompatible quality make the chitin and its derivatives particularly useful for biomedical applications such as wound healing, cartilage tissue engineering, drug delivery and nerve generation (NAGWA et al, 2004).…”
Section: Introductionmentioning
confidence: 99%